IS TIKTOK RECOMMENDED TO BE USED IN LEARNING? (Proceedings of the International Conference on Future of Education, 2023)
Social media has the potential to enhance the learning process. At the moment, students often use social media to study, including TikTok. However, most teachers said they were still hesitant about using TikTok for learning. Therefore, a literature review is necessary to provide an up-to-date overview of this platform. Based on the characteristics of social media which develop and change rapidly with the times, the researcher considers that rapid review is the right method to answer the questions asked. Articles were selected from the Wiley, ERIC, Taylor, and IEEE databases, with the following requirements: 1) published from 2020 onwards; 2) pass the peer review process, 3) be written in English and Indonesian. The article answers several questions: 1) What are the strategies to utilize TikTok for the learning process?; 2) How do students perceive Tiktok as a learning media?; 3) How do teachers perceive TikTok as learning media?. The results show that TikTok has been used in learning, it was shown from the total of 14 articles collected that have a good perception of the use of TikTok in learning. Therefore, students and teachers have shown positive responses about using TikTok for learning in this digital era.
Keywords: learning media; learning; social media; tiktok